Bahan dan Teknik Pembuatan Fragmen Gelang Kaca Samudera Pasai - Repelita Wahyu Oetomo (Balai Arkeologi Sumatera Utara, 2009)
AbstractGlass bracelets from Samudera Pasai is made using simple technology with low temperature combustion level. It’s possible that glass bracelets are the goods in a mass production to be accessible by the public. During that period, glassmaking technique with better quality has been known much earlier in other parts of Nusantara. Glass bracelets are also known by the name of Chettiar.